A study of logistics development in the Malaysia eastern region: A descriptive analysis. - Zuraimi Abdul Aziz; Mohd Rafi Yaacob; Mohamed Dahlan Ibrahim; Nur Fadiah Mohd Zawawi (2012)
This study investigated the current logistics development in The East Coast Region of Pennisular Malaysia. Logistics development is paramount important to the country in supporting economic and growth and enhancing competitiveness. Malaysia as well as many developing countries are still at the moderate stage in developing logistics systems and often face considerable challenges and constraints to provide efficient and effective logistics service. The respondents were from the different logistics players and there were 41 usable questionnaires were analyzed. This study found that the existing logistics infrastructures at the average level in this region. Amongst the constraints and challenges were professionalism in supporting the development, skill of manpower and financial issues in organization. Albeit all the constraints, most respondents were satisfied with the services rendered by logistics service providers.